Industrial Applications for Intelligent Polymers and Coatings - Hosseini, Majid; Makhlouf, Abdel Salam Hamdy; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book is a comprehensive collaboration on intelligent polymers and coatings for industrial applications by worldwide researchers and specialists. The authors cover the basis and fundamental aspects of intelligent polymers and coatings, challenges, and potential mechanisms and properties. They include recent and emerging industrial applications in medical, smart textile design, oil and gas, electronic, aerospace, and automobile industries as well as other applications including microsystems, sensors, and actuators, among others. The authors discuss the potential for future research in these areas for improvement and growth of marketable applications of intelligent polymers and coatings.
From the Contents: Basics and overview of intelligent polymers and coatings -- Techniques for the preparation, synthesis, and processing of intelligent polymers and smart coatings -- Modelling of intelligent polymers and smart coatings.
Keywords: Coatings; Tribology; Corrosion and anti-corrosives.; Polymers; Engineering design; Coatings; Tribology; Corrosion; Polymers; Engineering Design